Birds of a white feather : a congenital hypopigmentary disorder in the chick - Koubovec, Dominique Johanna (Division of Cell Biology, 2018)
Dominant white, a mutation of the I gene, leads to amelanosis and is common to many commercial breeds of fowl, including Pile Games, White Plymouth Rocks and White Leghorns. Despite much investigation on the cellular mechanisms of Dominant white, its mode of action is still poorly understood. The aim of this study is to elucidate the molecular basis of amelanosis in WPR X PG chickens by addressing the following two questions: are melanocytes present in the skin regions and feather follicles in normal numbers of 8- to 13-day white chick embryos? If melanocytes are present in normal numbers, are they unable to synthesise pigment because of a defect in melanocyte differentiation? Two approaches were used to answer the first question. MelEM, a monoclonal antibody, shown to react specifically to quail melanocytes, was found to be unsuitable for localisation of chicken melanocytes. Secondly, in situ hybridisation with tyrosinase and tyrosinase related protein-2 (TYRP2) probes was carried out to quantitate the number of melanocytes at different stages of development. The results indicate that tyrosinase - and TYRP2 -expressing melanocytes are present in 10-day white chick skin and feather buds in normal, if not greater numbers than in the control (Black Australorp) breed. This suggests that amelanosis is not due the failure of migratory melanoblasts to reach the developing feathers, nor is it due to the selective elimination of melanocytes during migration. The results further showed that with increasing developmental age (12- and 13-days), there is a decline in the number of tyrosinase - and TYRP2-expressing melanocytes in the white chick breed in comparison to the black breed. This suggests that white skin melanocytes either downregulate tyrosinase and TYRP2 gene expression yet remain viable, or they undergo cell death. At 17-days, the results showed an absence of gene expression in both the black and white follicles due to the normal process of feather development. Thus, although WPR x PG melanocytes are present in normal numbers in 10-day skin and feather follicles, they never melanise. To address this issue, black and white neural crest cells were cultured in conditions resembling their respective skin environments. Firstly, black neural crest cells grown in defined medium with either black or white skin extract were able to synthesise melanin. This suggests that white skin contains the appropriate signals necessary to induce melanogenesis of black melanocytes. This in turn suggests that the white melanocyte itself is intrinsically defective. To test this, white chick neural crest cells were grown in defined medium in the presence of black or white skin extract. The results showed that white cells were able to respond to signals in extracts of skin from both breeds and became melanised, suggesting that white melanocytes are not intrinsically defective. Due to the intricate nature of this study and subsequent experimental limitations encountered, these contradictory results could not be completely resolved. However, a testable model in which the I gene is postulated to encode c-kit is presented.